Answer:
The answers to the question are as follows
Initial a amount = 1
Decay Factor =0.99987
Decay rate = 1-0.99987 = 0.00013
Explanation:
We have the formula for exponential decay given by
In the above we have (1+b) = Decay factor
a = Initial amount
b = rate of decay
t = time
Comparing
, with the function in the question, we have
≡
Therefore, a ≡ 1,
1 + b ≡ 0.99987 and
x ≡ a
Therefore we have
Initial amount = 1
Decay/growth factor = 0.99987
But rate of decay = b = 1-(1-b) =b
Therefore Rate of Decay = 1 - 0.99987